Assembly of the Herpes Simplex Virus Procapsid from Purified Components and Identification of Small Complexes Containing the Major Capsid and Scaffolding Proteins - Newcomb, William W. (American Society for Microbiology, 1999)
An in vitro system is described for the assembly of herpes simplex virus type 1 (HSV-1) procapsids beginning with three purified components, the major capsid protein (VP5), the triplexes (VP19C plus VP23), and a hybrid scaffolding protein. Each component was purified from insect cells expressing the relevant protein(s) from an appropriate recombinant baculovirus vector. Procapsids formed when the three purified components were mixed and incubated for 1 h at 37°C. Procapsids assembled in this way were found to be similar in morphology and in protein composition to procapsids formed in vitro from cell extracts containing HSV-1 proteins. When scaffolding and triplex proteins were present in excess in the purified system, greater than 80% of the major capsid protein was incorporated into procapsids. Sucrose density gradient ultracentrifugation studies were carried out to examine the oligomeric state of the purified assembly components. These analyses showed that (i) VP5 migrated as a monomer at all of the protein concentrations tested (0.1 to 1 mg/ml), (ii) VP19C and VP23 migrated together as a complex with the same heterotrimeric composition (VP19C(1)-VP23(2)) as virus triplexes, and (iii) the scaffolding protein migrated as a heterogeneous mixture of oligomers (in the range of monomers to ∼30-mers) whose composition was strongly influenced by protein concentration. Similar sucrose gradient analyses performed with mixtures of VP5 and the scaffolding protein demonstrated the presence of complexes of the two having molecular weights in the range of 200,000 to 600,000. The complexes were interpreted to contain one or two VP5 molecules and up to six scaffolding protein molecules. The results suggest that procapsid assembly may proceed by addition of the latter complexes to regions of growing procapsid shell. They indicate further that procapsids can be formed in vitro from virus-encoded proteins only without any requirement for cell proteins.